2017
DOI: 10.1186/s13550-017-0315-y
|View full text |Cite
|
Sign up to set email alerts
|

Semi-quantitative metabolic values on FDG PET/CT including extracardiac sites of disease as a predictor of treatment course in patients with cardiac sarcoidosis

Abstract: BackgroundCardiac sarcoidosis is associated with major adverse cardiac events including cardiac arrest, for which anti-inflammatory treatment is indicated. Oral corticosteroid is the mainstay among treatment options; however, adverse effects are a major concern with long-term use. It would be beneficial for providers to predict treatment response and prognosis for proper management strategy of sarcoidosis, though it remains challenging. Fluorine (F)-18 fluorodeoxyglucose (FDG)-positron emission tomography(PET)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…FDG PET is a promising tool to assess the activity of CS. The volume-based assessment of FDG uptake is a more precise predictor of cardiac events than SUVmax [ 1 , 8 ]. An appropriate SUV threshold is important for the identification of the precise CMV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…FDG PET is a promising tool to assess the activity of CS. The volume-based assessment of FDG uptake is a more precise predictor of cardiac events than SUVmax [ 1 , 8 ]. An appropriate SUV threshold is important for the identification of the precise CMV.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoidosis is a multisystem disease pathologically characterized by non-caseating granuloma [ 1 6 ]. Cardiac sarcoidosis (CS) occasionally causes cardiac death via congestive heart failure, ventricular tachyarrhythmia, and advanced conduction disturbance [ 1 5 ]. 18 F-Fluorodeoxyglucose (FDG) is widely used as a positron emission tomography (PET) tracer to assess malignant and active inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Ishiyama et al reported that SUVmax over all sarcoidosis-involved organs better predicted response to oral corticosteroids than tCMA in patients with CS. 19 LGE in CMR has been shown to be a strong predictor of cardiac events in patients with proven systemic sarcoidosis even in patients with preserved LVEF. 20,21 Bravo et al studied PET and CMR in patients with clinical manifestations of CS and found that LGE predicted cardiac events similarly in PETpositive and PET-negative patients.…”
Section: Discussionmentioning
confidence: 98%